Teachers’ Degree of Practicing Social Responsibility at Imam Abdulrahman Bin Faisal University, Saudi Arabia - Baniawwad, Abdelmonim H. (Frontiers in Education, 2022)
The study aims to identify the social responsibility practiced by the faculty members towards the students, university, and society at the Imam Abdul Rahman bin Faisal University, Saudi Arabia. Data was collected through a random sampling of 951 students. The findings reveal that the faculty members are practicing social responsibility and that the most important thing for the faculty members is to inculcate social responsibility among the students by encouraging them, involving them in social and cultural activities, and exercising democratic values. The participants agree that faculty members should maintain university equipment, contribute to seminars and conferences inside and outside of the university, and maintain a safe environment. The participants agreed that faculty members should participate in the activities of cultural associations and institutions, respect cultural diversity, and get involved in community development. The theoretical and practical implications of the study have been identified to improve social responsibility at the higher institutions in Saudi Arabia as well as in the Gulf-region.